2004
DOI: 10.1057/palgrave.jt.5740134
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation and financial performance of English professional football clubs

Abstract: British soccer has become a large, high-profile industry, but it is constantly dogged by accusations of poor management practices at club level. Yet there are few explorations into what kind of management practices would be most suitable for this industry. In this paper, the authors explore the possible financial benefits that have accrued to English professional football clubs that have developed their market orientation.The research estimates market orientation scores for 26 clubs (28 per cent of the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The study of the dynamics of share prices of football teams is an important research field within the financial economy of the football clubs, certainly given the greater volatility of such securities inevitably linked to sports results [25,7,9,32,5,6,13], to the management and strategic actions undertaken by the companies [19], to the potentially profitable market of the football companies [24], to the soccer players' performance and skills and coaches [18,11]. Empirical research shows that a good performance of the football title is generally preceded by a good sporting result [6] and, therefore, the link between sports results and stock market performance in European football seems particularly marked [25,3,5,14,4,23,16,20].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The study of the dynamics of share prices of football teams is an important research field within the financial economy of the football clubs, certainly given the greater volatility of such securities inevitably linked to sports results [25,7,9,32,5,6,13], to the management and strategic actions undertaken by the companies [19], to the potentially profitable market of the football companies [24], to the soccer players' performance and skills and coaches [18,11]. Empirical research shows that a good performance of the football title is generally preceded by a good sporting result [6] and, therefore, the link between sports results and stock market performance in European football seems particularly marked [25,3,5,14,4,23,16,20].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The Premier League's big six are Manchester United, City, Liverpool, Arsenal, Chelsea, and Spur. The selection of the Big Six is based on [21], which states that British football largely represented by the big five clubs (now big six) face paradox, closer relationship with sponsorship and media generate more revenues but must spend much for talented players and have left a high debt. Second, the club is not a listed company.…”
Section: A Population Sample and Datamentioning
confidence: 99%
“…Some studies have investigated the financial performance of football clubs in several countries for example [1], [2] in Greek, [18], [19] in Turkey, [3] in Italy, [10], [12] in France, [11] in Czech, [20] in Spanish, [4], [9], [21] in UK., and [8], [13], [22] in European continent. Different from [20], which uses only Altman [15] model, the present study also utilizes other measurements of bankruptcy, i.e., Springate [16] and Zmijewski [17], to see the consistency of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Performance management and measurement systems for soccer clubs are inevitable and very crucial to success in the industry. Previous studies have mainly focused on financial performance (Ozawa, Cross, & Henderson, 2004;Kern & Süssmuth, 2005;Barros & Leach, 2006;Manuel Luiz & Fadal, 2011;Morrow, 2013;Rossi, Thrassou, & Vrontis, 2013;Özaydin, & Donduran, 2019) or the sporting performance of soccer clubs Kraus, & Messner, 2016;Adams, Morrow, & Thomson, 2017). In other studies, Parganas, Liasko and Anagnostopoulos (2017) indicated the importance of performance in multiple fields and discussed the relationship between social media success, commercial success, and team performance; Chadwick (2009) discussed the "on-field/off-field" dichotomy; Georgievski, Labadze, and Aboelsoud, (2019) analysed offensive and defensive performance in the field; and Cornwell, Pruitt, and Van Ness (2001) linked on-field and off-field performance.…”
Section: Performance Management Of Soccer Clubsmentioning
confidence: 99%